Renegotiation of Sales Contracts - Steven A. Matthews (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
Contracts adopted with later renegotiation in mind may take simple forms. In a principal-agent model, if renegotiation may occur after the agent chooses efforet, the principal protects against unfavorable renegotiation by "selling the project" to the agent via a sales contract. If only singleton (single-scheme) contracts are feasible, the equilibrium initial contract must be a sales contract if the principal's renegotiation position will be inherently inferior in the sense that (a) the agent will have the bargianing power; (b) the principal will not observe the agent's effort, and (c) the agent has the talent, i.e. a rich set of feasible efforts, to exploint contractual nuances. Renegotiation necessarily occurs, and it yields (second-best) efficient allocations. Even when meny (multiple-scheme) contracts are available, if the selection of a scheme from a menu entails any cost, then the final contract is a singleton and equilibrium renegotiation occurs. If there is any complexity cost to specifying a menuy, the initional contract must also be a singleton; it is necessarily a sales contract if the agent has talent. A weak forward induction refinement criterion is used to obtain these results.
Keywords: D21; D82; C72; 330; contracts; principal-agent; moral hazard; renegotiation; incentives